Reading the rubbish dump as a heterotopia in Neill Blomkamp's district 9. (3rd May 2020) - Jones, Megan
ABSTRACT: I read the rubbish dumps of Neill Blomkamp's 2009 film District 9 in order to think about how peripheral places and communities can reframe the South African city. In the film, dumps are sites of abandonment and transformation. This doubleness exemplifies Michel Foucault's privileged site, the heterotopia. I focus on two scenes that take up little of the film's running time but speak to the possibilities of the dump as more than simply a space of immiseration. The scenes unsettle orthodoxies of space that define the postapartheid city and reposition the heterotopic dump at the urban centre rather than the margins.